HUBUNGAN KEMAMPUAN MATEMATIKA DAN KEMAMPUAN IPA MAHASISWA PGSD FIP UNIVERSITAS NEGERI MAKASSAR KAMPUS VI BONE - Sudarto, Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the correlation between students' mathematical abilities and science abilities. The population of this study were te students of the PGSD Department of FIP Makassa State University, the 6th Campus of Bone, Class of 2020, in totaling of 60 students. The data analysis technique were descriptive and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was found that the average mathematics and science abilities of students were 41.43 and 57.80 and the based on inferential statistical analysis it was found that the correlation coefficient value for students' mathematics and science abilities was of 0.858 and the sig. (two parties) value was of 0.000. Because the Sig value. < α/2 (with α=0.05) then H1 was accepted. The results of the research can be concluded that there is a relationship between students' mathematical abilities and students' natural science abilities: (1) the type of connection is unidirectional, meaning that if the students' mathematical abilities increase, the students' natural science abilities also increase or if the students' natural science abilities increase, the students' mathematical abilities also increase and (2) the relationship between mathematics ability and students' science ability is very strong and significant